2021
DOI: 10.33275/1727-7485.1.2021.663
|View full text |Cite
|
Sign up to set email alerts
|

Ice sheet velocity tracking by Sentinel-1 satellite images at Graham Coast Kyiv Peninsula

Abstract: The study of Antarctic glaciers and ice sheets velocity is one of the most discussed topics. Such high interest in this topic is primarily because the ice from the Antarctic glaciers, which gets to the ocean, significantly affects the ocean level and the global climate. Development of modern satellite technologies for Earth remote sensing made it possible to elaborate a number of methods for ice sheets’ displacements estimation and calculation of such displacements velocities. This work uses remote sensing dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Accor ding to satellite observations of 105 glaciers in the west part of the Antarctic Peninsula from 2014 to 2021, the average acceleration of the movement of ice masses in summer was 12.4 ± 4.2%, and the maximum acceleration was 22.3 ± 3.2% (Wallis et al, 2023). The ice velocity determination within the Kyiv Peninsula confirmed that the speed of glacier movements can reach 3.5-4 m/day (Kadurin & Andrieieva, 2021).…”
mentioning
confidence: 59%
“…Accor ding to satellite observations of 105 glaciers in the west part of the Antarctic Peninsula from 2014 to 2021, the average acceleration of the movement of ice masses in summer was 12.4 ± 4.2%, and the maximum acceleration was 22.3 ± 3.2% (Wallis et al, 2023). The ice velocity determination within the Kyiv Peninsula confirmed that the speed of glacier movements can reach 3.5-4 m/day (Kadurin & Andrieieva, 2021).…”
mentioning
confidence: 59%